Hypoxia-Exosome Mesenchymal Stem Cells Therapy Reduces Interleukin-6 Levels and CD86 Expression - Isfandiari, Adelia Bayu; Putra, Agung; Setiawan, Eko (Molecular and Cellular Biomedical Sciences, 2025)
Background: UVB exposure activates type 1 macrophages (CD86) and increases IL-6, both contributing to collagen loss. exosome hypoxia mesenchymal stem cells (EH-MSC) has anti-inflammatory properties, suggesting its potential role in modulating CD86 activation and IL-6 secretion. This study examines the effects of EH-MSC injections on CD86 and IL-6 levels in UVB-exposed skin with collagen loss.Materials and methods: Experimental research post-test only control group design was conducted with 30 male Wistar rats (Rattus norvegicus, strain: Wistar Han) divided into five groups. G1: healthy rats, G2: UVB-exposed with a subcutaneous injection of 0.9% NaCl, G3: UVB-exposed with Hyaluronic Acid, and G4 & G5: UVB-exposed with EH-MSC injections of 200 µL and 300 µL, respectively. IL-6 and CD86 levels were analysed using ELISA and qRT-PCR at 14 days post-treatment continue with statistical analysis.Results: IL-6 analysis showed that levels in G4 (107.70±47.86 pg/mL) and G5 (58.68±25.37 pg/mL) were notably lower than in G2 and G3 (p<0.05). Compared to G1 (32.28±14.65 pg/mL), G4 exhibited a statistically distinct increase (p<0.05), whereas G5 showed no significant difference (p>0.05). Meanwhile, CD86 data analysis showed that G4 (0.53±0.14 pg/mL) were lower than in G1 (1.03±0.01 pg/mL) and G2 (1.47±0.43 pg/mL), but not significantly different from G3 (0.87±0.1 pg/mL) and G5 (0.36±0.08 pg/mL). Similarly, CD86 expression in G5 decreased relative to G1 and G2 (p<0.05) but remained similar to G3 and G4.Conclusion: EH-MSC injections (200 µL and 300 µL) significantly reduced IL-6 and CD86 levels in collagen loss rats, supporting its potential as a therapeutic approach for UVB-induced skin damage.Keywords: collagen loss, CD86, EH-MSC, IL-6, UVB